Saru Pakareman: Refleksi Pengalaman Diri sebagai Practice-led Research - Ananda, Rizky Fauzy; Limbong, Helena Evelin; Budiawan, Hery (Resital: Jurnal Seni Pertunjukan, 2022)
ABSTRACT This research on the art creation of Saru Pakareman's work aims to find the importance of repetition in both musical and extra-musical. This work is a process of creating musical compositions that depart from the reflection of the researcher's self-experience.  This art creation research activity is based on musical and extra-musical experiences in the researcher's life that have an influence on the researcher's music writing style or language. These experiences are mostly found by researchers from everyday life from childhood in the realm of family (social) phenomena where the influence of cultural teachings brought by mothers plays a major role in the process of self-introduction and the researcher's musical style. The art creation research methodology used is Practice-led Research artistic research which is also integrated with ethnographic and phenomenological approaches. The stages carried out a) the collection of data on phenomena, minimalist music, repetitions, Sundanese, and drum patterns, b) deepening of art creation: Repetition, Art creation Internship, Laboratory, and Curation. The results of this art creation research are in the form of program music works based on family socio-cultural phenomena and repetitions with simple development, interpretation of laras saléndro padantara into the whole tone scale in Western music, as well as the transition of traditional musical instruments kendang, karawitan degung laras madenda, and karawitan jaipong into the form of a string ensemble presentation. The results of such art creation research prove that the importance of repetition in music as well as in the context of life. Without repetitions in music a piece will not sound musical, while in the context of life repetition is something that always exists in everyday life such as worship activities and life patterns, in the context of education repetition is the easiest and most basic way of learning to learn and recall about understanding something. Reflection on life-experience through Practice-led Research is proven to be an idea of art creation research and is able to bridge the gap between subjectivity and objectivity in scientific writing.ABSTRAK Penelitian penciptaan karya Saru Pakareman ini bertujuan untuk menemukan arti pending repetisi baik dalam musikal maupun ekstra-musikal. Karya ini merupakan proses penciptaan komposisi musik yang berangkat dari refleksi pengalaman diri penulis. Kegiatan penelitian penciptaan ini didasari oleh pengalaman musikal dan ekstra-musikal dalam hidup penulis yang memiliki pengaruh terhadap gaya atau bahasa penulisan musik penulis. Pengalaman pengalaman tersebut sebagian besar didapati penulis dari kehidupan sehari-hari sedari kecil dalam ranah fenomena (sosial) keluarga di mana pengaruh ajaran kebudayaan yang dibawa oleh ibu berperan besar dalam proses pengenalan diri dan gaya musik penulis. Metodologi penelitian penciptaan yang digunakan adalah penelitian artistik Practice-led Research yang juga diintegrasikan dengan pendekatan etnografi dan fenomenologi. Tahapan yang dilakukan: a) Pengumpulan data mengenai fenomena, musik minimalis, repetisi, Sunda, dan pola kendang; b) Pendalaman penciptaan: repetisi, magang penciptaan, laboratorium, dan kurasi. Hasil penelitian penciptaan ini berupa karya musik program yang didasari oleh fenomena sosial budaya keluarga dan repetisi dengan pengembangan sederhana, penginterpretasian laras saléndro padantara ke dalam whole tone scale dalam musik barat, serta peralihan wahana instrumen musik tradisional kendang, karawitan degung laras madenda, dan karawitan jaipong ke dalam bentuk sajian ansambel gesek. Hasil dari penelitian penciptaan tersebut membuktikan bahwa pentingnya repetisi dalam musik maupun dalam konteks kehidupan. Tanpa adanya repetisi dalam musik suatu karya tidak akan terdengar musikal, sedangkan dalam konteks kehidupan repetisi adalah hal yang selalu ada dalam keseharian seperti kegiatan peribadatan maupun pola hidup, dalam konteks Pendidikan repetisi merupakan cara belajar termudah dan paling dasar untuk mempelajari dan mengingat kembali tentang pemahaman sesuatu. Refleksi atas pengalaman diri lewat Practice-led Research terbukti dapat dijadikan sebuah ide penelitian penciptaan dan mampu menjembatani antara subjektifitas dan objektifitas dalam penulisan ilmiah.